Detection of Fungal Pathogen and Loss Assessment of Maize (Zea mays L.) Seeds at Storage Conditions Around Jimma, South Western Ethiopia - Regasa, Gizachew Hirpa; Amare, Dereje (International Journal For Research In Agricultural And Food Science, 2019)
Maize is the primary staple crop and it’s grown nearly in all agro-ecological zones of Ethiopia. Despite the steady production of maize over the past several decades, post-harvest losses of maize remained significant. Post-harvest handling, poor infrastructure, weather variability, biotic factors such as insect pests, bacteria, viruses, and fungi, often aggravate such losses. There is an increasement in consumption of contaminated grain with mycotoxins which causes different health problems including death. Therefore, the present study was designed to quantify postharvest losses and detection of fungal diseases infecting maize seeds at storage conditions. Loss assessment were done by taking two hundred seed from each five sample of maize seeds collected randomly. The study was conducted at the Jimma University College of Agriculture and Veterinary Medicine in plant pathology laboratory. The experiment had five treatments and three replications with completely randomized design (CRD) arrangements. The overall Maize grain losses was 32.3% whereas 20.7%, 2.6% and 9.0% where loss of Insect damage, broken and mould respectively. The highest postharvest losses were recorded in retailer seed from Limmu area 77.5% losses. Among the storage fungal pathogens Fusarium, Aspergillus and Penicillium are the most predominant species attacking maize seed and resulting in reduction in seed germination. The highest fungal frequency were Fusarium spp. of the three major storage pathogens of maize seed collected. In the agar plate were recorded 56.66 %, 40.67% and 23.33%, Fusarium spp., Aspregilus spp. and Penicillium spp. respectively. In Blotter method the highest fungal frequency was Aspregilus spp. with 39.33% followed by Fusarium spp.and Penicilium spp. with 36.67% and 16.0% respectively. Therefore, giving attentions to those pathogens associated with postharvest fungal pathogen will help in the reduction of molds and mycotoxins development.